Effects of Organic Solvent Doping on the Structural and Conductivity Properties of PEDOT: PSS Fabric. Issue 1 (1st January 2022) - Ayub, Ayu Natasha; Ismail, Nur Atikah; Aizamddin, Muhammad Faiz; Bonnia, Noor Najmi; Sulaiman, Noor Safina; Nadzri, Nur Izzati Muhammad; Mahat, Mohd Muzamir
Abstract: The development of highly conductive fabrics for application in electronic textiles on non-rigid substrates has gained much interest owing to their potential for realizing next-generation wearable conductive fabrics. Besides, it could be used as a portable device in the energy and healthcare industries. However, pristine PEDOT: PSS has been reported to have low conductivity values due to excessive PSS chains that wrapped up around the PEDOT conductive chain structure. In this context, one of the most successful techniques to include dopant is to use ethylene glycol (EG) to improve the conductivity of poly (3, 4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS). Immersing or coating of fabrics with PEDOT: PSS is one of the facile methods used for obtaining functional and smart properties. Our studies prepared conductive polymer; PEDOT: PSS with ethylene glycol (EG) dopant) at different concentrations on polyester (PES) fabric substrates by a facile immersion process. The effect of the different concentrations of EG on the conductivity is shown when Electrochemical Impedance Spectroscopy (EIS) is conducted. It shows that 6% v/v of EG gives the optimum conductivity value up to 4.06 × 10 -3 Scm -1 . Meanwhile, Scanning Electron Microscopy (SEM) imaging is focusing on the morphology of the immersed fabric. The improvement in crystallinity of the doped PEDOT: PSS was revealed and evaluated using X-ray Diffraction (XRD). As a result, it has been demonstrated that EG is an excellent dopant because it efficiently increases the electrical conductivity and crystallinity of PEDOT: PSS fabric.